9-Methylfascaplysin Is a More Potent Aβ Aggregation Inhibitor than the Marine-Derived Alkaloid, Fascaplysin, and Produces Nanomolar Neuroprotective Effects in SH-SY5Y Cells - Qingmei Sun; Fufeng Liu; Jingcheng Sang; Miaoman Lin; Jiale Ma; Xiao Xiao; Sicheng Yan; C. Benjamin Naman; Ning Wang; Shan He; Xiaojun Yan; Wei Cui; et al. (Marine Drugs, 2019)
β-Amyloid (Aβ) is regarded as an important pathogenic target for Alzheimer’s disease (AD), the most prevalent neurodegenerative disease. Aβ can assemble into oligomers and fibrils, and produce neurotoxicity. Therefore, Aβ aggregation inhibitors may have anti-AD therapeutic efficacies. It was found, here, that the marine-derived alkaloid, fascaplysin, inhibits Aβ fibrillization in vitro. Moreover, the new analogue, 9-methylfascaplysin, was designed and synthesized from 5-methyltryptamine. Interestingly, 9-methylfascaplysin is a more potent inhibitor of Aβ fibril formation than fascaplysin. Incubation of 9-methylfascaplysin with Aβ directly reduced Aβ oligomer formation. Molecular dynamics simulations revealed that 9-methylfascaplysin might interact with negatively charged residues of Aβ42 with polar binding energy. Hydrogen bonds and π⁻π interactions between the key amino acid residues of Aβ42 and 9-methylfascaplysin were also suggested. Most importantly, compared with the typical Aβ oligomer, Aβ modified by nanomolar 9-methylfascaplysin produced less neuronal toxicity in SH-SY5Y cells. 9-Methylfascaplysin appears to be one of the most potent marine-derived compounds that produces anti-Aβ neuroprotective effects. Given previous reports that fascaplysin inhibits acetylcholinesterase and induces P-glycoprotein, the current study results suggest that fascaplysin derivatives can be developed as novel anti-AD drugs that possibly act via inhibition of Aβ aggregation along with other target mechanisms.